pH – to Be or not to Be: A Study in Retrospect - Johansson, Stig R. (European Journal of Scientific Exploration, 2019)
Uncertainty concerning what H+ really should stand for hampers a sufficiently clear apprehension of the chemical "superstar", pH. Basically, pH is a kind of designation for "hydrogen ion concentration" (Luo et al., 2019: 4976; Farsad and Goldsmith, 2016: 1-6). As a designation, at least, it is well known to ordinary people, but not so "how" and "why" (Murmiliuk et al., 2018: 1243). A common notion is that pH is a measure of acidity, indeed even among chemists themselves. This misconception is surprising in view of the fact that the quantity being tampered with is a very basic one: concentration, often denoted [X]. The most used dimension is moles per litre, M. The uncertainty begins with X; it is, we are told, the ubiquitous "hydrogen ion". So far so good. But dealing with, e. g., [H3O+] = 10-7 M for processes in neutral water may be disturbingly impractical. Taking the logarithm gives the number -7 instead. But the minus sign is not to our liking either, thus "7". An epistemologically comprehensive description of "pH" in all its aspects does not seem to exist. What follows is an attempt to fill the gap, if any. By keeping the real ion H(H2O) and the fictive proton, H+, apart, perhaps a thorough understanding of the pH quantity might prevent questions like "what is pH of ammonia in air" from being asked and textbook statements like "a pH scale being devised" (Dillard and Goldberg, 1978: 38-73), not to mention discouraging test results among students (Olander, 2007).